Greek Women’s Knowledge and Perceptions Related to Breast Cancer Prevention (International Journal of Nursing Education, 2022)
Background: Breast cancer is the most common form of cancer and the leading cause of cancer death in womenworldwide. The aim of this survey was to investigate Greece women’s knowledge and perceptions related tobreast cancer prevention.Methods: A reliable questionnaire from the literature was used which then was translated using the forward andbackward translation method. It contained 37 questions and the sample consisted of 650 women. The statisticalanalysis was completed using SPSS 25. The study found that the majority of the sample had knowledge regardingbreast cancer prevention, they knew the importance of breast self-examination and annual clinical breastexamination needed to be conducted as well as the age to undergo their first mammogram. Age, occupation,annual family income, education level, and marital status significantly influenced women’s knowledge andperceptions related to breast cancer prevention.Conclusions: The state, the media and schools contribute to raising awareness and the involvement of healthprofessionals is essential to better inform and educate adolescent girls and women on this issue.
Keywords: Breast cancer, Health professionals, Prevention.